RENCANA BISNIS RUMAH FISIOTERAPI KOTAGEDE - , Elly Widyastuti; , Boyke R. Purnomo, S.E., M.M., CFP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Physiotherapy is a branch of health science that is implemented in the form of health services targeted at individuals and groups to develop, maintain and restore movement and function throughout the life cycle of the body. One embodiment of the health care will be included in a business plan to formalize the establishment of a physiotherapy practice in Yogyakarta, which will be named Rumah Fisioterapi Kotagede (RFK). In the preparation of the business plan, internal and the external environment will be analyzed and evaluated, as well as the use of the concept of strategy and business plan functionally. The concept of the establishment is that physiotherapy is offered for the convenience of patients, physiotherapist friendliness and provide affordable prices for the community. The concept of interior design and layout of space will be tailored to the targeted market segments of children aged 0-5 years and elderly people with age above 56 years. With the business plan, it is expected to provide an overview of the strategic steps in building this business which includes marketing planning, operational planning, human resource planning and financial planning. Finance analysis includes company performance projections and investment feasibility calculation for the next five years which gives Net Present Value (NPV) Rp. 656.370.242,-, Internal Rate of Return (IRR) 17.30% and Payback Period (PP) 2,03 years. Based on the analysis of all aspects of the business, this business plan is for realizing whether this practice is feasible or not.